ANALISIS KEAMANAN DATA DENGAN ALGORITMA ADVANCED ENCRYPTION STANDARDS (AES) DAN RIVEST SHAMIR ADLEMAN (RSA) - Ahmat Setiawan (INFO-TEKNIK, 2025)
In an increasingly interconnected digital era, data security has become a critical aspect across various sectors such as banking, government, and the technology industry. Threats to information, including hacking and data theft, have driven the need for encryption technology as a primary solution for data protection. This study aims to analyze the effectiveness of two widely used modern cryptographic algorithms—Advanced Encryption Standard (AES) and Rivest-Shamir-Adleman (RSA)—in safeguarding digital data. AES is a symmetric algorithm that operates on 128-bit data blocks, while RSA is an asymmetric algorithm that relies on the complexity of factoring large prime numbers. This study compares the strengths and weaknesses of both algorithms in terms of encryption efficiency, resilience against cyberattacks, and their implementation in information technology systems such as digital banking services, cloud computing, and online transactions. Through a literature review, this research seeks to provide a comprehensive understanding of the role of cryptography in addressing information security challenges in the digital age.